Optimization of Taste-Masked (–)-Oleocanthal Effervescent Formulation with Potent Breast Cancer Progression and Recurrence Suppressive Activities - Tajmim, Afsana (Pharmaceutics, 2019)
S-(–)-Oleocanthal (OC), a naturally occurring phenolic secoiridoid exclusively found in extra-virgin olive oil (EVOO), is a potential nutraceutical therapeutic for inflammation, neurodegenerative diseases, and many malignancies, especially breast cancer (BC). The oral delivery of OC is challenging because of its irritative, bitter, and pungent taste and exceptional chemistry, including two reactive aldehydes, phenolic, and ester groups. OC irritation did not correlate with CO(2)-induced irritation, and hence, OC was not exerting generalized acid-sensing irritation. The objective of this study was to develop an effervescent formulation of OC with an effective CO(2)-induced masked taste maintaining the efficacy against the estrogen receptor (ER) and HER2 positive BC. Several ratios of acid and carbonate sources were screened, and five effervescent formulations EF1-EF5 were selected and prepared based on their pH and effervescence time. OC formulations were characterized using differential scanning calorimetry, FT-IR spectroscopy, and scanning electron microscopy analyses. OC formulations exhibited acceptable flowability and effervescence time. Based on physical characteristics and improved OC release, formulation EF-2 was selected for subsequent studies. EF-2 showed effective OC taste masking, as suggested by electronic artificial tongue and mouse preference tests. EF-2 suppressed more than 70% of the hormone and HER2-positive BT-474 BC cell growth in a nude mouse xenograft model. Furthermore, EF-2 demonstrated significant inhibition of BT-474 tumor cell locoregional recurrence after primary tumor surgical excision. EF-2-treated mouse sera had significantly reduced CA 15-3 levels, the human BC recurrence marker, compared to the placebo control group at the end of the study. These results highlight the potential of the OC formulation EF-2 as a prospective nutraceutical for the control and prevention of ER(+)/HER(+) BC progression and locoregional recurrence.